Features of Motivation of the Educational Activity of Pupils (Theoretical Aspect) - E S Babayeva (Peoples' Friendship University of Russia (RUDN University), 2008)
The article discloses the concepts «motive», «motivation», their correlation, stages of motives. It also examines the features of struggle of motives in the educational activity of schoolchildren. In the course of the analysis of their works, groups with high, average and low levels of motivation have been singled out in the article.